Evaluation of propensity score used in cardiovascular research: a cross-sectional survey and guidance document. Issue 8 (26th August 2020) - Samuel, Michelle; Batomen, Brice; Rouette, Julie; Kim, Joanne; Platt, Robert W; Brophy, James M; Kaufman, Jay S
Abstract : Background: Propensity score (PS) methods are frequently used in cardiovascular clinical research. Previous evaluations revealed poor reporting of PS methods, however a comprehensive and current evaluation of PS use and reporting is lacking. The objectives of the present survey were to (1) evaluate the quality of PS methods in cardiovascular publications, (2) summarise PS methods and (3) propose key reporting elements for PS publications. Methods: A PubMed search for cardiovascular PS articles published between 2010 and 2017 in high-impact general medical (top five by impact factor) and cardiovascular (top three by impact factor) journals was performed. Articles were evaluated for the reporting of PS techniques and methods. Data extraction elements were identified from the PS literature and extraction forms were pilot tested. Results: Of the 306 PS articles identified, most were published in Journal of the American College of Cardiology (29%; n=88), and Circulation (27%, n=81), followed by European Heart Journal (15%; n=47). PS matching was performed most often, followed by direct adjustment, inverse probability of treatment weighting and stratification. Most studies (77%; n=193) selected variables to include in the PS model a priori. A total of 38% (n=116) of studies did not report standardised mean differences, but instead relied on hypothesis testing. For matching, 92% (n=193) of articles presented the balance of covariates. Overall, interpretations of the effect estimates corresponded to the PS method conducted or described in 49% (n=150) of the reviewed articles. Discussion: Although PS methods are frequently used in high-impact medical journals, reporting of methodological details has been inconsistent. Improved reporting of PS results is warranted and these proposals should aid both researchers and consumers in the presentation and interpretation of PS methods.